Age‐related changes in behavior profile in male offspring of rats treated with poly I:C‐induced maternal immune activation in early gestation - Tengfei Chen; Huadan Meng; Ni Fang; Peiling Shi; Mengxue Chen; Qing Liu; Luxian Lv; Wenqiang Li (Animal Models and Experimental Medicine)
Abstract Background Autism and schizophrenia are environmental risk factors associated with prenatal viral infection during pregnancy. It is still unclear whether behavior phenotypes change at different developmental stages in offspring following the activation of the maternal immune system. Methods Sprague–Dawley rats received a single caudal vein injection of 10 mg/kg polyinosinic:polycytidylic acid (poly I:C) on gestational day 9 and the offspring were comprehensively tested for behaviors in adolescence and adulthood. Results Maternal serum levels of interleukin (IL)‐6, IL‐1β and tumor necrosis factor‐α were elevated in poly I:C‐treated dams. The offspring of maternal poly I:C‐induced rats showed increased anxiety, impaired social approach, and progressive impaired cognitive and sensorimotor gating function. Conclusion Maternal immune activation led to developmental specificity behavioral impairment in offspring.